‘Value, values and valued’: a tripod for organisational ethics - Mohindra, Raj (Journal of medical ethics, 2022)
Public benefit corporations are National Health Service, that is, state, entities whose function to provide healthcare in discharge of public duties. If we regard value as the output of such organisations, it seems logical to connect the values of the organisation to the value produced by such organisations. But, on closer examination there are competing underlying logics in play: (1) those based on promoting organisational efficiency and efficacy; and (2) those based on the idea of building service provision around the clinician-patient relationship. Underlying these logics are differing value sets. These clash. Because of the clashing of underlying moral frameworks the connection between values and value becomes hard, if not impossible. This paper argues that (1) the clash in these moral frameworks must be addressed by the organisation rather than between individuals or groups of individuals within the organisation; (2) alloying duties within hybrid professionals submerges but does not resolve these conflicts; (3) one approach could be to impose on the organisation itself an ethical imperative to promote, enhance and protect from deterioration the welfare of the patients; (4) a board ethics committee is a possible organisational structure that could transparently and fairly balance clashes within the competing moral frameworks in a way that could reconcile the competing logics and (5) if such conflicts can be better resolved at the organisational level what the organisation must do to achieve its objectives will become clearer because what needs to be valued would naturally emerge connecting values, value and what is valued.